Nevi, family history and fair skin increase the risk of second primary melanoma - Siskind, Victor (2010)
While risk factors for primary cutaneous melanoma are well defined, relatively little is known about predictors for second primary melanoma. Given the rising incidence of this cancer, coupled with improvements in survival, there is a prevalent and growing pool of patients at risk of second primary melanomas. To identify the predictors of second primary melanoma, we followed a cohort of 1083 Queensland patients diagnosed with incident melanoma between 1982-90 and who completed a baseline questionnaire. During a median follow-up of 16.5 years, 221 patients were diagnosed with at least one additional primary melanoma. In multivariate analyses, second primary melanomas were associated with high nevus count (HR 2,91, 95%CI 1,94 - 4.35), high familial melanoma risk (2.12, 1.34-3.36), fair skin (1.51, 1.06-2.16, inability to tan (1.66, 1.13-2.43), an in situ first primary melanoma (1.36, 0.99-1.87) and masculine sex (1.49, 1.12-2.00) Patients whose first primary was lentigo maligna melanoma (1.80, 1.05-3.07) or nodular melanoma (2.13 , 1.21-3.74) had higher risks of subsequent primaries than patients whose first primary tumor was superficial spreading melanoma. These characteristics could be assessed in patients presenting with first primary melanoma to assess their risk of developing a second primary.